Plurilinguisme à l’école : aperçus du projet NEW ABC sur la formation des enseignants en tant que processus participatif - Rosa Pugliese; Greta Zanoni; Maria Cecilia Andorno; Paolo Della Putta; Silvia Sordella (Recherches en didactique des langues et des cultures)
Despite the fact that the European and Italian contexts are equipped with guidelines and tools for multilingual education, the latter struggles to enter curricular teaching activities. This article presents a pilot action on teacher training to multilingual education, as part of a larger European project (NEW ABC, Networking the Educational World: Across Boundaries for Community-building) whose conviction is that genuine educational transformation can result from involving teachers as direct participants in the design of new pedagogical possibilities. The pilot action we discuss here is therefore a concrete application of the PAR (Participatory Action Research) methodology in the sphere of multilingual education. We illustrate the various phases of the intervention: from context analysis to participatory observation of pedagogical practices, to moments of co-construction of activities with the teachers. In conclusion we present, as an example, a co-constructed activity, thus attempting to show the outcomes of a PAR-inspired teacher training course.